Analisis Strategi Pemasaran Dengan menggunakan Metode SWOT dan Analytical Hierarchy Process (AHP) untuk Meningkatkan Volume Penjualan - Virly Kania Puteri; Dwi Astuti (GLOBAL SCIENTS PUBLISHER, 2025)
Effective marketing strategy analysis is the key for companies to achieve growth and success in business. In this article, we outline a methodical and structured approach to developing a marketing strategy by combining the SWOT (Strengths,Weaknesses,Opportunities, Threats) and AHP (Analytical Hierarchy Process) methods. We detail practical steps to identify a company's strengths,weaknesses, opportunities, and threats, and develop appropriate marketing strategies based on the SWOT analysis findings. Through case studies and qualitative research, we explore various strategies that businesses can implement to increase their sales. The results of a SWOT analysis serve as a basis for creating a marketing plan that takes advantage of the company's internal strengths and external opportunities, while overcoming internal weaknesses and taking advantage of external opportunities